Adaptive mHealth Intervention for Adolescent Physical Activity Promotion. (23rd January 2021) - Cushing, Christopher C; Bejarano, Carolina M; Ortega, Adrian; Sayre, Nick; Fedele, David A; Smyth, Joshua M
Abstract: Objective: The present nonrandomized controlled trial aimed to evaluate feasibility, acceptability, and preliminary efficacy of a tailored text message intervention for increasing adolescent physical activity, as compared with passive monitoring. Methods: Forty adolescents (13–18 years old) received either a tailored text messaging intervention (Network Underwritten Dynamic Goals Engine [NUDGE]; N  = 20), or participated in an attention-control condition ( N  = 20), for 20 days. Physical activity was measured for all participants via continuous accelerometry. Frequency analyses were conducted on program usage and satisfaction ratings to evaluate feasibility and acceptability, and multilevel models were used to evaluate the efficacy hypotheses. Results: The vast majority of participants (90%) reported being very or mostly satisfied with the NUDGE program and rated their enjoyment as above average. The intervention group was estimated to spend an average of 20.84 more minutes per day in moderate-to-vigorous physical activity relative to the attention-control group ( β = 20.84, SE = 8.19). Exploratory analyses revealed that the intervention group also engaged in 82 fewer minutes of sedentary time per day on average, although this effect was not significant due to the large variability in sedentary time ( β = −81.98, SE = 46.86). Conclusions: The NUDGE tailored text messaging intervention was feasible, acceptable, and efficacious in increasing physical activity in this sample. Findings warrant additional evaluation of NUDGE as both a standalone physical activity intervention or as part of a multicomponent package.